2021
DOI: 10.1016/j.ultsonch.2021.105507
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-mediated gene delivery into suspended plant cells using polyethyleneimine-coated mesoporous silica nanoparticles

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…This shows the impact of silica nanoparticle concentration on germination rate. Furthermore, the recent research by Maryam et al [118] is worth mentioning, where the researchers developed poly-ethyleneimine (PEI) coated MSNs. The particles were loaded with genetic material (pDNA) for an efficient and successful transfection to plant cells via ultrasonic treatment.…”
Section: Agricultural Applications Of Snpsmentioning
confidence: 99%
“…This shows the impact of silica nanoparticle concentration on germination rate. Furthermore, the recent research by Maryam et al [118] is worth mentioning, where the researchers developed poly-ethyleneimine (PEI) coated MSNs. The particles were loaded with genetic material (pDNA) for an efficient and successful transfection to plant cells via ultrasonic treatment.…”
Section: Agricultural Applications Of Snpsmentioning
confidence: 99%
“…Its main application is as a nonviral vector for DNA transfer in gene therapy, including regenerative medicine [78], AIDS, cancer, and hereditary disorder treatments [79]. It has also been used for transfection and editing of genomes in plants [84,85], as well as for the gene silencing systems mentioned above aimed at disease and pest control [22,47,52,86,87].…”
Section: Polyplex Nanoparticlesmentioning
confidence: 99%
“…Another oligonucleotide of interest for therapeutic applications is plasmid DNA (pDNA) delivery. Since pDNA is typically circular and thus contains no terminal end to serve as a conjugation handle, the most common delivery methods rely on either cationic moieties [62,70,71] or encapsulation. [72,73] However, Beals et al demonstrated a strategy for plasmid delivery by incorporating a biotin group into the sequence of an EGFP plasmid for covalent conjugation to streptavidin-functionalized gold nanoparticles.…”
Section: Oligonucleotide Attachmentmentioning
confidence: 99%